An argumentative environment for design and a case study in database design - Pal, Sumit; Batanov, Dentcho N.; Tabucanon, Mario T.; Lefevre, Thierry; The Government of Norway (NORAD) (Bangkok : Asian Institute of Technology, 1995)
This work presents a new and novel technique to aid the process of collaborative database design using an argumentative approach, based on a theory of Argumentation. The work presents the architecture of an integrated, collaborative design environment, that automates the process of database design after resolving the design deliberations. It tries to identify the conclusive arguments using argumentation framework. The design space is based on the Issue Based Information System concept. It investigates into the different stages of conceptual database design namely, the identification of entities, attributes and the relationships.
A thesis submitted in the partial fulfillment of the requirements for the degree of Master of Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1995
Keywords: Database design